1998
DOI: 10.1073/pnas.95.22.13176
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP 3 A 4 genotype with treatment-related leukemia

Abstract: Epipodophyllotoxins are associated with leukemias characterized by translocations of the MLL gene at chromosome band 11q23 and other translocations. Cytochrome P450 (CYP) 3A metabolizes epipodophyllotoxins and other chemotherapeutic agents. CYP3A metabolism generates epipodophyllotoxin catechol and quinone metabolites, which could damage DNA. There is a polymorphism in the 5 promoter region of the CYP3A4 gene (CYP3A4-V) that might alter the metabolism of anticancer drugs. We examined 99 de novo and 30 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
153
3
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(173 citation statements)
references
References 61 publications
8
153
3
8
Order By: Relevance
“…These results demonstrate that, in Brazilians, CYP3A4*1B and CYP3A4*1A have a peculiar distribution. Although many studies have connected CYP3A4 genotypes with ethnicity (36,40,41,(46)(47)(48), in this study the genotype distribution revealed no correlation with patient skin color. Besides this, it was observed that the GG genotype was twice as common in non-white people (66.7%).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…These results demonstrate that, in Brazilians, CYP3A4*1B and CYP3A4*1A have a peculiar distribution. Although many studies have connected CYP3A4 genotypes with ethnicity (36,40,41,(46)(47)(48), in this study the genotype distribution revealed no correlation with patient skin color. Besides this, it was observed that the GG genotype was twice as common in non-white people (66.7%).…”
Section: Discussioncontrasting
confidence: 69%
“…Clinical research (47) and in vitro functional analysis (25,48) generated controversial results concerning the affects of carrying CYP3A4-V. Studies of patients with the wild-type genotype (CYP3A*1A or CYP3A4-W) found that these individuals may be at an increased risk of treatmentrelated leukemia. The authors suggested that it may be a result of epipodophyllotoxin and other chemotherapeutic agent metabolism by CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP 1A1 variants, i.e., CYP 1A1*2A and *2B, have been shown to have increased activity and to be a genetic risk factor in certain types of cancer [7]. CYP 3A4*1B, the promotor variant of CYP 3A4, is also known to be associated with the risk of therapyrelated leukemia in childhood ALL with MLL rearrangement [8]. Recently, genetic polymorphisms and the expression of CYP 3A5 have been described [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of certain polymorphisms in detoxifying enzymes is associated with increased risk of secondary AML. 12,13 Most previous studies have analyzed all types of secondary malignancies, 14,15 but there are few comprehensive large-scale studies specifically on secondary hematological malignancies. Furthermore, most reports on secondary hematological malignancies focus on second leukemias only.…”
mentioning
confidence: 99%